ROLE OF TRANSFORMATIONAL LEADERSHIP FOR GOOD GOVERNANCE AND SUSTAINABLE DEVELOPMENT IN NIGERIA (Journal of the Management Sciences, 2024)
The predicament of Nigeria in terms of underdevelopment can be linked to the problem of leadership and governance. The objectives of the study is on the issue of transformational leadership and good governance in the actualization of the overall development in Nigeria, for the for the purpose of well-being of all in the society. Data for this study were chiefly secondary sources. The disillusionment on bad leadership and governance in Nigeria is the crux for the study. It is pertinent therefore, to note that every nation (developed and developing) continuously strive to meet the expectations of her citizens, while upholding her core values and ethics. Admittedly, visionary and transformational leadership is a role model key to unlock any meaningful sustainable development of a contemporary society. The study anchors on Erickson theory of motivation and clients' needs as a framework for analysis. The paper identified corruption, lack of political will on the part of leaders and lack of patriotism in the rule of law in national service as the major disruptions and constraints to good governance and sustainable development in the society. It recommends above all, the need for quality education for all and proper leadership training, patriotism and value reorientation on the part of individuals and political leaders as part of solutions to the above problems. Transformational leadership and good governance is affective for motivation, revival and national development in Nigeria, especially in this present situation of the country where so much is going wrong against the ethics.
Keywords: Transformational leadership, motivation, good governance, sustainable development.